Connecting to Work : How Information and Communication Technologies Could Help Expand Employment Opportunities - Raja, Siddhartha; Imaizumi, Saori; Kelly, Tim; Narimatsu, Junko; Paradi-Guilford, Cecilia (World Bank, Washington, DC, 2013)
Information and communication technology (ICT) has grown as a sector and now employs millions of people worldwide. The proliferation of ICTs has also helped digitize how people find and do work. The world will need to create over 600 million jobs by 2030 for unemployment to remain at current levels. ICT-enabled employment may help address some of this problem both by creating jobs in the ICT sector and by helping to make labor markets more inclusive, innovative, flexible, and transparent. What can governments do to prepare for these changes and maximize employment opportunities? This paper is a first step in an effort by the World Bank to understand how ICTs are shaping, changing, and transforming labor markets. It explores how governments and other stakeholders might respond to leverage the growth of ICTs to help increase employment opportunities. This paper is structured as follows: section 1 serves as an introduction; section 2 defines the scope, focusing on the types of employment opportunities due to ICT as a sector and as a tool; section 3 considers the impact of the ICT sector on software programming, IT services, and telecommunications; section 4 describes how ICTs as tools empower and include more workers in labor markets; section 5 analyzes the challenges and risks that appear alongside these opportunities; section 6 discusses human capital, infrastructure, financial, regulatory, and social systems that will enable ICT in employment; and section 7 identifies strategic themes for governments to consider as they maximize the gains from ICT's increasing role in the world of work.